Mechanisms underlying the impact of exercise training in pulmonary arterial hypertension. (January 2018) - Nogueira-Ferreira, Rita; Moreira-Gonçalves, Daniel; Santos, Mário; Trindade, Fábio; Ferreira, Rita; Henriques-Coelho, Tiago
Abstract: Pulmonary arterial hypertension (PAH) is a devastating disease characterized by progressive increases in pulmonary vascular resistance that can ultimately lead to right ventricle failure and death. Common symptoms include shortness of breath, fatigue, dizziness and chest pain, which negatively impact the functional capacity and quality of life. Despite the improvements in disease-targeted therapies, PAH remains incurable and with a high mortality rate, requiring effective therapeutic strategies. Exercise training is an important adjunct non-pharmacological treatment for patients with left heart failure and chronic obstructive pulmonary disease. Although exercise training was discouraged in PAH because of safety concerns, recent studies support that supervised exercise training is safe and beneficial in patients with stable PAH. However, the molecular mechanisms underlying these improvements are still poorly understood. This review summarizes and integrates the emerging clinical and experimental studies describing the molecular alterations related with exercise training in PAH. Graphical abstract: Highlights: Different molecular mechanisms appear to be modulated by exercise training in heart, lungs and skeletal muscle. Exercise training may modulate RV hypertrophy, preventing the progression to RV failure. Exercise training can be related with a decrease in the maladaptive pulmonary vascular remodelling. Exercise training seems to be a valuable approach in the management of PAH.